Kingdom of the Netherlands-Netherlands : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Following several years of expansion, the Dutch economy is in its third year of weak growth. Executive Directors commended the authorities on prudent economic policy, and advised for fiscal consolidation in view of population aging. They welcomed the multiyear fiscal framework, and underscored the need to press forward with labor and product market reforms. They appreciated the sound fiscal and structural policies. They agreed that the Dutch financial sector remained sound and well supervised, and commended authorities for taking measures to strengthen the public finances.